COMPARISON BETWEEN PROPORTIONAL INTEGRAL DERIVATIVE (PID) AND MODEL PREDICTIVE CONTROL (MPC) FOR SHIP HEADING CONTROL - Jannaty, Baity; Muhammadun, Muhammadun; Mustaqim, Kiki (Kadikma, 2023)
In this paper discussed about ship heading control problem. Ship heading control is one of the ship control problem in the application in the marine field. With rudder angle as input control, the heading angle controlled therefore it can reach reference heading angle with minimum energy. Assume that is wave disturbance to the system. We compare two method for control the heading angle, that is Proportional Integral Derivative (PID) and Model Predictive Control (MPC). Proportional Integral Derivative (PID) is a controller that determine the presition of an instrumentation system with feedback characteristic on the system. MPC is a control technique, which embeds optimization within feedback to deal with systems subject to constraints on inputs and states. From the simulation result, MPC can compansate the disturbance better than PID. The time to reach reference angle when controlled using MPC faster than using PID. The change value of Np also almost give same result. But the change parameter PID can give very difference result seen from the rise time, the settling time, and the overshoot.